ANTHRACYCLINE CARDIOTOXICITY: THE PHARMACOKINETICS AND PHARMACODYNAMICS OF DEXRAZOXANE AND ITS OPEN RING METABOLITE. (21st November 2014) - Jirkovska-Vavrova, A; Jirkovsky, E; Stariat, J; Jansova, H; Roh, J; Lencova-Popelova, O; Kovarikova, P; Sterba, M; Simunek, T
Abstract : The toxic effects of anthracycline antineoplastic drugs to cardiomyocytes is a a serious drawback of their high antineoplastic efficiency. Dexrazoxane remains the only clinically approved protective substance against the cardiotoxicitity of anthracycline antineoplastic drugs. Although the mechanisms of the cardioprotection are elusive so far, widely accepted hypothesis represents dexrazoxane as a pro-drug yielding an EDTA-like metabolite ADR-925. By chelating iron, ADR-925 could prevent oxidative damage induced by anthracyclines. However, the relationship of dexrazoxane hydrolysis and its cardioprotective activity is only poorly characterised. We found that the rate of dexrazoxane decay (100 µM) to ADR-925 in the culture medium does not change in the presence of the cardiomyocytes. We also observed that ADR-925 passes through the plasma membrane into the cells, although more slowly than dexrazoxane. In cells ADR-925 chelates free intracellular iron. Also ADR-925 is able to displace iron from its complex with anthracyclines in solution. Interestingly, both dexrazoxane and ADR-925 were found to interact with topoisomerase II in cells, although in a different manner. The plasma and tissue concentrations of dexrazoxane and ADR-925 were measured also using validated analytic methods in plasma, myocardium, soleus muscle, liver and urine samples after a one dose of dexrazoxane and ADR-925 to rabbits (60 mg/kg, i.p.) and fundamental pharmacokinetic parameters were calculated. We documented that ADR-925 crosses the plasma membrane and also interacts with the topoiosomerase II beta in cardiomyocytes. These findings together with the in vivo data provide a valuable insight into the pharmacokinetic/pharmacodnamic relationship of the dexrazoxane cardioprotection of anthracycline cardiotoxicity.